Vocal and articulatory speech control deficits in individuals with post-stroke aphasia - Roozbeh Behroozmand; Zeinab Khoshhal Mollasaraei; Vahid Nejati; Ayoub Daliri; Julius Fridriksson (Scientific Reports)
Abstract Individuals with post-stroke aphasia exhibit deficits in regulating vocal (i.e., laryngeal) pitch control during speech vowel production; however, it is not determined whether such deficits also exist when they control their supra-laryngeal speech articulators during word production. To address this question, 19 subjects with post-stroke aphasia and 20 controls were tested under an altered auditory feedback paradigm in which they received + 30% shifts in their vowel first-formant frequency during word production. In addition, 17 aphasia subjects and 19 controls from the same groups also completed steady vowel vocalizations while receiving randomized pitch shifts at ± 100 cents. Consistent with previous findings, our data showed that the magnitude of compensatory vocal responses to pitch-shifted vowel productions was significantly reduced in individuals with aphasia vs. controls. In addition, we also found that the magnitude of compensatory articulatory responses to formant-shifted vowels during word production was significantly diminished in the aphasia group compared with controls. However, no significant correlation was found between the vocal and articulatory compensatory responses to pitch and formant alterations. These findings suggest that vocal and articulatory motor speech control are regulated via independent mechanisms, and stroke-induced damage to left-hemispheric brain networks can selectively impair them in stroke survivors with aphasia.